Virtual borders, real laws [Internet activity and treaties]. - Banisar, D.
National governments are working to tame activity on the Internet. They have worked steadily to extend control over online activities that they believe affect their interests, even when the activities occur outside their borders. These usually involve what governments regard as their domain: protecting public order, enforcing commercial laws, and, occasionally, protecting consumer interests. Methods have included assertions or legal jurisdiction based on where material is accessible instead of where it originates, and the blocking of sites, service providers, or entire high level domains from access by citizens. Such instances are mentioned in this article. Whilst larger companies are able to defend themselves against overseas lawsuits, individuals and smaller organizations lack the resources to defend what are often normal business activities at home, but could violate the laws of local jurisdictions in countries around the world. The problems of libel are discussed as are the blocking of certain sites by certain countries. Efforts to draw up Internet treaties are also mentioned.
Keywords: Internet activity; Internet sites blocking; Internet treaties; Commercial laws enforcement; Consumer interests protection; Lawsuits; Legal jurisdiction; National governments; Online activities; Public order protection